A Soybean Resistant Protein-Containing Diet Increased the Production of Reg3γ Through the Regulation of the Gut Microbiota and Enhanced the Intestinal Barrier Function in Mice - Ogita, Tasuku; Namai, Fu; Mikami, Ayane; Ishiguro, Takahiro; Umezawa, Koji; Uyeno, Yutaka; Shimosato, Takeshi (Frontiers in Nutrition, 2021)
The maintenance of intestinal homeostasis is necessary for a good quality of life, and strengthening of the intestinal barrier function is thus an important issue. Therefore, we focused on soybean resistant protein (SRP) derived from kori-tofu (freeze-dried tofu), which is a traditional Japanese food, as a functional food component. In this study, to investigate the effect of SRP on the intestinal barrier function and intestinal microbiota, we conducted a SRP free intake experiment in mice. Results showed that ingestion of SRP decreased the serum level of lipopolysaccharide-binding protein and induced the expression of Reg3γ, thereby improving the intestinal barrier function. In addition, SRP intake induced changes in the cecal microbiota, as observed by changes in -diversity. In particular, in the microbiota, the up-regulation of functional gene pathways related to the bacterial invasion of epithelial cells (ko05100) was observed, suggesting that Reg3γ expression was induced by the direct stimulation of epithelial cells. The results of this study suggest that SRP is a functional food component that may contribute to the maintenance of intestinal homeostasis.